GASTRIC FUNDIC GLAND POLYPS: CAN HISTOLOGY BE USEFUL TO PREDICT PROTON PUMP INHIBITORS USE? - BRITO,Hugo Leite de Farias (2018)
ABSTRACT BACKGROUND: Fundic gland polyps allegedly increased in frequency in recent decades, and had attracted great attention due to possible association with prolonged proton pump inhibitor therapy. Prolonged use of this drug could cause parietal cell hyperplasia, obstruction of glandular lumen and cystic dilation of the gland. OBJECTIVE: This study aims to analyze clinical and pathological features of fundic gland polyps in patients with and without proton pump inhibitor therapy in a selected population from Brazil. METHODS: It was selected a sample of 101 Brazilian patients (78 females and 23 males), from a five years retrospective search of the files from a private pathology laboratory. The patients had an average age of 57 years and we included patients with a histological diagnosis of fundic gland polyp. The clinical data were obtained from their files and all histological slides were reviewed and examined with hematoxylin and eosin (HE) and Giemsa. RESULTS: Information about the use or non-use of proton pump inhibitors (PPI) was obtained in 84 patient files. In 17 cases we could not determine if PPI were used or not. Among those in which the information was available, a positive history of anti-acid therapy was observed in 63 (75.0%) patients. Parietal cell hypertrophy/hyperplasia and parietal cell protrusions were detected in most slides. Histological findings were identical in PPI users and PPI negative patients. Helicobacter pylori infection was detected in just two samples. Epithelial dysplasia or adenocarcinoma were not observed in our cases. Histopathological analysis of fundic gland polyps could not distinguish between PPI and non-PPI related cases. Parietal cell cytoplasmic protrusions, an alleged marker of prolonged acid suppression therapy, was detected in both groups. CONCLUSION: Histological features could not discriminate anti-acid therapy related fundic glands polyps in our patients.